Le nom propre en chinois. Essai de morphosyntaxe - Pierre de La Robertie (Corela)
The author presents some basic characteristics of the Chinese language and Chinese writing, including the pinyin romanization of this language. First of all, there is no space between words, no Capital letters, nothing, to distinguish Proper Names and other kinds of words, except if one uses romanization. Only the place of the word in the sentence, the syntactic function of the word (or phrase), or its meaning, may show that this is a Proper Name. Speaking about Geographical Names, the author divides its presentation into two parts: endonyms and exonyms. The Chinese endonyms follow administrative rules: specific term first, generic term second. The generic terms are mostly made of only one syllable. Rules for writing endonyms in romanization are exposed in details too. The specific and generic terms are separately written, but for names of villages and other small entities. The reality in newspapers and books are different from what is decreted by Governmental organisations: very often the generic term is omitted, this situation may create ambiguity. About exonyms (this category comprises foreign terms as well as terms in minority languages), the situation is complex: one cand find transcription, translation or a mix of both technics. When the foreign Generic term is meaningful, it is usually translated by its Chinese equivalent, the Specific term is translated by Chinese characters whose sound is as near as possible from the original equivalent, there are Administrative norms asking people to use always the same character to write such or such foreign syllable. The Names of persons are usually written with the family name first, the personal name second. The combination of patronyms and idyonyms form most often three syllables, the choice of the personal name is a complicated thing for the parents, because each are meaningful and highly regarded. The foreign names are only transcripted, for a long time there was no rules, each writer following its own way, which could create a lot of complications, the Government has these last few years issued regulations for names originally in French, in English, in German, Russian, in Arabic and other languages and writing. What makes reading difficult is the fact that a Chinese character is always meaningful, but one has to forget its meaning to understand the foreign name, either Geographical or Personal.